The impact of fast food marketing on brand preferences and fast food intake of youth aged 10-17 across six countries - Mariangela Bagnato; Marie-Hélè; Lana Vanderlee; Christine White; David Hammond; Monique Potvin Kent (BMC, 2023)
Abstract Background Consumption of fast food, which is associated with poor diet, weight gain and the development of noncommunicable diseases, is high amongst youth. Fast food marketing, a modifiable determinant of excess weight and obesity, affects youth's food-related behaviours. This study aimed to examine the relationship between exposure to fast food marketing and the fast food brand preferences and intake amongst youth aged 10-17 across six countries. Methods Data from 9,695 youth respondents living in Australia, Canada, Chile, Mexico, the United Kingdom (UK) and the United States (US) were analyzed from the 2019 International Food Policy Study (IFPS) Youth Survey. Survey measures assessed exposure to fast food marketing and brand-specific marketing, and preference for these brands and fast food intake. Regression models adjusted for age, sex, income adequacy and ethnicity were used to examine the associations. Results Exposure to fast food marketing was positively associated with brand preferences and intake consistently across most countries. Overall, preference for McDonald's (OR:1.97; 95% CI:1.52, 2.56), KFC (OR:1.61; 95% CI:1.24, 2.09) and Subway (OR:1.73; 95% CI:1.34, 2.24) were highest when exposed to general fast food marketing ≥ 2x/week compared to never. Preference for McDonald's (OR:2.32; 95% CI:1.92, 2.79), KFC (OR:2.28; 95% CI:1.95, 2.68) and Subway (OR:2.75; 95% CI:2.32, 3.27) were also higher when exposed to marketing for each brand compared to not. Fast food intake was highest in Chile (IRR:1.90; 95% CI:1.45, 2.48), the UK (IRR:1.40; 95% CI:1.20, 1.63), Canada (IRR:1.32; 95% CI:1.19, 1.48), Mexico (IRR:1.26; 95% CI:1.05, 1.53) and the US (IRR:1.21; 95% CI:1.05, 1.41) when exposed to general fast food marketing ≥ 2x/week compared to never and was higher across most countries when exposed to brand-specific marketing compared to not. Respondents classified as ethnic minorities were more likely to report consuming fast food than ethnic majorities, and females were less likely to report consuming fast food than males. Conclusions Exposure to fast food marketing is consistently and positively associated with brand preferences and fast food intake in all six countries. Our results highlight the need for strict government regulation to reduce exposure of unhealthy food marketing to youth in all six countries.